Direct Measurements of Momentum Flux and Dissipative Heating in the Surface Layer of Tropical Cyclones During Landfalls. Issue 10 (17th May 2018) - Ming, Jie; Zhang, Jun A.
Abstract: This study analyzes high‐frequency wind data collected by research towers in the surface layer of Typhoons Hagupit (2008) and Chanthu (2010) to investigate the characteristics of the momentum flux, turbulent kinetic energy (TKE), drag coefficient, and dissipative heating (DH) during landfalls. It is found that the momentum flux TKE and DH increase with the wind speed up to the maximum observed wind speed (~40 m/s), in agreement with previous studies that presented eddy correlation flux data in a similar condition but with lower maximum observed wind speed. However, the momentum flux, TKE, drag coefficient, and DH are found to be substantially larger in Typhoon Chanthu (2010) than those in Typhoon Hagupit (2008) at a given wind speed, likely due to much rougher surface conditions surrounding the tower deployed in Typhoon Chanthu (2010). Furthermore, the DH is calculated using two different methods: (1) based on surface‐layer theory and (2) based on the standard turbulent spectra method. It is found that the first method tends to overestimate the value of DH compared to the second method, and the overestimation of the DH by the first method is much smaller over rougher underlying surface than over the smoother underlying surface. Our analysis shows that the magnitude of the DH over land is as large as the sensible heat flux (~100 W/m 2 ) previously observed over the ocean, which should not be neglected in numerical models simulating tropical cyclones during landfalls. Key Points: Direct measurements of momentum flux, drag coefficient, and TKE are substantially larger in coastal regions with larger surface roughness Dissipative heating (DH) estimated using the theoretical method is generally larger than that estimated using the spectra method The overestimation of DH by the theoretical method is much smaller over the coastal land than over the shallow water at a given wind speed